ANALISIS HUBUNGAN ASPEK BUDAYA DAN PERAN PETUGAS PROMKES TERHADAP PEMBERIAN ASI EKSKLUSIF - F, Nur Gilang; Hayati, Nur; Waru, Hamsia L.; Ramli, Ramli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Exclusive breastfeeding is an important policy in improving infant and maternal health. Senaning Health Center is one of the health centers located in the border area and has a problem in the low coverage of exclusive breastfeeding. In 2022 the achievement of exclusive breastfeeding was only 48%. The purpose of the study was to determine the relationship between cultural aspects and the role of health promotion officers on exclusive breastfeeding. The research design used in this study was cross sectional. The research was conducted in the Senaning Health Center working area. The research was conducted in April 2024. The study population was all mothers who had babies aged 6-12 months, totaling 68 people. The sample amounted to 68 people. The sampling technique used total sampling. Data analysis was done univariate and bivariate. The results showed a relationship between cultural aspects (p value: 0.000) and the role of health promotion officers (p value: 0.003) on exclusive breastfeeding. It is recommended that health workers can improve health promotion strategies such as conducting home visits and counseling for pregnant women and breastfeeding mothers regarding exclusive breastfeeding during posyandu.Keywords: Exclusive breastfeeding, culture, health promotion officers.